2018
DOI: 10.1016/j.ccell.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

EWS/FLI Confers Tumor Cell Synthetic Lethality to CDK12 Inhibition in Ewing Sarcoma

Abstract: Many cancer types are driven by oncogenic transcription factors that have been difficult to drug. Transcriptional inhibitors, however, may offer inroads into targeting these cancers. Through chemical genomics screening, we identified that Ewing sarcoma is a disease with preferential sensitivity to THZ1, a covalent small-molecule CDK7/12/13 inhibitor. The selective CDK12/13 inhibitor, THZ531, impairs DNA damage repair in an EWS/FLI-dependent manner, supporting a synthetic lethal relationship between response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 44 publications
(72 reference statements)
4
124
0
1
Order By: Relevance
“…Except for MV4-11 cells, the cell lines tested exhibited a low sensitivity to PARPi, with an IC50 in the micromolar range (Figure S7A), an order of magnitude higher than what is reported for other cancer cells in vitro, such as a BRCA1/2-deficient breast cancer cell line (Farmer et al, 2005). We examined cell viability after four days of treatment, and used two different methods to assess possible synergistic effects between PRMT5i and PARPi: the Bliss synergy method (He et al, 2018; Iniguez et al, 2018) (Figure 7B), and the Chou-Talalay method (Chou, 2010) (Figure S7B). We observed positive Bliss scores for all cell lines tested (Figure 7B), indicating a synergistic effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for MV4-11 cells, the cell lines tested exhibited a low sensitivity to PARPi, with an IC50 in the micromolar range (Figure S7A), an order of magnitude higher than what is reported for other cancer cells in vitro, such as a BRCA1/2-deficient breast cancer cell line (Farmer et al, 2005). We examined cell viability after four days of treatment, and used two different methods to assess possible synergistic effects between PRMT5i and PARPi: the Bliss synergy method (He et al, 2018; Iniguez et al, 2018) (Figure 7B), and the Chou-Talalay method (Chou, 2010) (Figure S7B). We observed positive Bliss scores for all cell lines tested (Figure 7B), indicating a synergistic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Bliss synergy was calculated using the bioconductor package synergyfinder v1.0.0 using default parameters for calculating bliss independence (He et al, 2018). Excess over bliss was calculated as the difference between the observed response and the expected bliss independence (Iniguez et al, 2018). …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they are characterized by an increased sensitivity to cisplatin and thus represent potential biomarker for treatment response [29][30][31][32][33]. Although inactivation of CDK12 kinase activity clearly leads to HR defects and sensitivity to PARP inhibitors in cells [21,[34][35][36][37], the discovery of the CDK12 inactivation-specific tandem duplication phenotype indicated a distinct function of CDK12 in maintenance of genome stability. The size and distribution of the tandem duplications suggested that DNA replication stress-mediated defect(s) are a possible driving force for their formation [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…This response correlates with decreased U1 snRNP levels, with the resultant intronic polyadenylation 60 . Conceivably, the effects we attribute to CDK12 inhibition may not be limited to cells with underlying DNA damage such as NB and possibly Ewing sarcoma 16 , but also in cancers with CDK12 loss-of-function mutations such as ovarian cancer. Indeed, as recently demonstrated in a subset of prostate cancers with CDK12 loss-of-function mutations 14 , the PCPA, as well as intron retention, observed with CDK12 inhibition could facilitate the formation of neoantigens that could be exploited to improve immune therapies or to develop personalized cancer vaccines 61 .…”
Section: Inhibition Of Cdk12 By Thz531 Results In Increased Transcripmentioning
confidence: 99%
“…The selective regulation of these genes by CDK12 is also evident in cancers with loss-of-function CDK12 mutations, such as high-grade serous ovarian carcinoma and metastatic castration-resistant prostate cancer, where a 'BRCAness' phenotype with genomic instability sensitizes cells to DNA cross-linking agents and poly (ADP-ribose) polymerase (PARP) inhibitors [11][12][13][14] . Similarly, suppression of wild-type CDK12 in Ewing sarcoma cells driven by the EWS/FLI fusion oncoprotein using THZ531 15 (a selective inhibitor of CDK12/13) also led to the decreased expression of DDR genes 16 . Hence, CDK12 loss of function, whether spontaneous or induced, appears to preferentially affect genes that have prominent roles in DNA repair and consequently in maintaining the stability of the genome.…”
mentioning
confidence: 99%